TINJAUAN KECENDERUNGAN KEUSAHAWANAN DALAM KALANGAN PELAJAR DI INSTITUSI PENGAJIAN TINGGI AWAM - Mutalib, Salmianti (Journal of Techno-Social, 2013)
In this era of globalization, entrepreneurship field is certainly crucial as it is playing its role as the catalyst of the economy and the ability to the effort in increasing the innovation, creativity and competitiveness in a particular country. In line with this, entrepreneurship field is highly expanded in Malaysia through our country education system. This study was done to investigate the tendency of entrepreneurship among the students in public higher educational institution. The design of this study is in descriptive with using quantitative approach. Survey method was chosen as the study instruments by using Likert Scale. The data of this survey was analyzed by using Statistical Packages for Social Sciences (SPSS) version 20. The respondents consist of 80 of Bandar Penawar Community College students that were chosen randomly. Based on the findings, it was shown that motivational factor is the main factor that influences students in the tendency towards the entrepreneurship field. Besides, it was also found out that there is no significant difference for the tendency items based on gender factors, residential places and family background.